Student Perspectives on Virtual-Based Simulation Practicum: Challenges and External Factors at SMKN 10 Makassar - Hendra Jaya; Irma Tamrin; Indar Winardy; M. Arham; Aqri Dwi Aqram; Mustamin; Saharuddin; Putri Ida Sunaryathy Samad (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2026)
Purpose - This study explores students’ perspectives on virtual simulation-based practicum learning at SMKN 10 Makassar, focusing on challenges and external factors affecting learning effectiveness. Methods - A mixed-method approach was used, combining descriptive quantitative analysis with qualitative data. Participants were 39 eleventh- and twelfth-grade students from electronics and mechatronics programs. Data were collected through Likert-scale questionnaires and semi-structured interviews, then analyzed using descriptive statistics and thematic analysis based on the Attride-Stirling Thematic Network framework. Findings - Most students showed positive perceptions of virtual simulation learning, particularly in digital literacy and application use. About 64.1% were familiar with digital technology in learning, and 56.4% could independently operate simulation applications. However, challenges remained, including fear of making mistakes, limited understanding of concepts and digital instructions, lack of virtual practicum experience, and low confidence in using technology. External factors such as family support, device access, internet quality, and digital media use also influenced learning success. Research Implication - Virtual simulation practicum learning requires more than reliable technology. Schools must strengthen students’ digital literacy, self-efficacy, and learning support through interactive strategies, continuous scaffolding, accessible infrastructure, and adaptive instructional design. Originality - This study highlights vocational students’ direct perspectives on virtual simulation practicum learning and shows how both internal factors, such as confidence and digital literacy, and external factors, such as family support and internet access, shape learning effectiveness.